Pisma Józefa Goldszmita w kontekście wyborów życiowych Janusza Korczaka - Sęczek, Marlena (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article is an attempt to answer the question of what influence attorney Józef Goldszmit (1844–1896) had on the life path chosen by his son Henryk Goldszmit, known as Janusz Korczak. Through an analysis of selected articles and pamphlets by Józef Goldszmit, published mainly in the post-Haskalah press, the author attempts to reconstruct Korczak’s father’s views on the role of the Jewish intelligentsia in the life of the Israeli nation, and the model of the personal pattern of a Jewish citizen inherent in his works.